A qualitative study to explore traffic police personnel perceptions towards road safety behaviour among young riders in Manipal, India - Kumar Sumit; Kris Brijs; Veerle Ross; Geert Wets; Robert A. C. Ruiter (BMC, 2024)
Abstract Road crash injuries are significant public health issues in many low-and middle-income countries. Every year more than 1.35 million people lose their lives due to road crashes, making it one of the leading causes of death worldwide. In 2021, 1.19 million road traffic deaths occurred worldwide. Globally, India accounts for the second-largest number of fatal road traffic crashes. Riders in the age range of 18-25 years contribute to 41.4% of India's total road crash victims. An in-depth understanding of the current traffic density, violations, and behaviours of young riders is essential for enforcement agencies, in particular, the traffic police personnel. Their perspective is relevant as they have a unique position to judge and evaluate the riding behaviours and the efficiency of the existing intervention programmes. Furthermore, their suggestions can be highly effective in developing evidence-based risk reduction programmes. The present study was conducted in Manipal, which is a locality of Udupi district in Karnataka province of Southwestern India. Seventeen in-depth interviews were conducted from October 2018 to January 2019 among traffic police personnel. Thematic analysis was done using ATLAS.ti 8 software to identify, analyse, and report themes within the data. Respondents revealed that in recent times Manipal roads have become unsafe for young riders. Factors such as speeding, using a mobile phone while riding, reckless riding, and overtaking from the wrong side were the main reasons for road traffic crashes. Interventions like the installation of traffic barricades, closed-circuit television cameras, speed breakers, and signboards at the crash hotspots, together with strict enforcement of traffic laws, were suggested by the respondents to reduce crashes. The study findings highlight the importance of traffic police personnel's views in understanding the various determinants for road crashes observed among young riders. Future research can be taken up in other settings with broader age group involvement for the target population. There is a need to establish a coordination committee that can locally organize awareness programmes involving all the stakeholders on road safety to increase the level of risk perception and reduce crashes.